Two Distinct Modes of PERIOD Recruitment onto dCLOCK Reveal a Novel Role for TIMELESS in Circadian Transcription. - Sun, W.C.; Jeong, E.H.; Jeong, H.J.; Ko, H.W.; Edery, I.; Kim, E.Y. (Journal of Neuroscience, 2010)
Negative transcriptional feedback loops are a core feature of eukaryotic circadian clocks and are based on rhythmic interactions between clock-specific repressors and transcription factors. In Drosophila, the repression of dCLOCK (dCLK)-CYCLE (CYC) transcriptional activity by dPERIOD (dPER) is critical for driving circadian gene expression. Although growing lines of evidence indicate that circadian repressors such as dPER function, at least partly, as molecular bridges that facilitate timely interactions between other regulatory factors and core clock transcription factors, how dPER interacts with dCLK-CYC to promote repression is not known. Here, we identified a small conserved region on dPER required for binding to dCLK, termed CBD (for dCLK binding domain). In the absence of the CBD, dPER is unable to stably associate with dCLK and inhibit the transcriptional activity of dCLK-CYC in a simplified cell culture system. CBD is situated in close proximity to a region that interacts with other regulatory factors such as the DOUBLETIME kinase, suggesting that complex architectural constraints need to be met to assemble repressor complexes. Surprisingly, when dPER missing the CBD (dPER(?CBD)) was evaluated in flies the clock mechanism was operational, albeit with longer periods. Intriguingly, the interaction between dPER(?CBD) and dCLK is TIM-dependent and modulated by light, revealing a novel and unanticipated in vivo role for TIM in circadian transcription. Finally, dPER(?CBD) does not provoke the daily hyperphosphorylation of dCLK, indicating that direct interactions between dPER and dCLK are necessary for the dCLK phosphorylation program but are not required for other aspects of dCLK regulation.